ATTITUDES OF THE SLOVAK UNIVERSITY OF TECHNOLOGY STUDENTS TO THE CREATION AND PROTECTION OF THE ENVIRONMENT - RUSKOVA, Dagmar; VASKOVA, Lubica (The Eurasia Proceedings of Educational and Social Sciences, 2017)
The paper addresses the level of environmental and ecological literacy of the students of Slovak University of Technology in Bratislava. The authors deal with literacy in stated area in three synergetic dimensions: cognitive, emotional and conative. In the cognitive level are mapped the general knowledge of students regardless of the technical field of their studies. They analyze students' views on teaching at the Technical University from the viewpoint of the need for clarity and acceptability of the effect of technology on the environment not only "here and now", but with a time lag of several years or decades. By the Semantic differential method, they try to find the answer to the question about the quality of students' attitudes to the issue of development and environmental protection. They identify explicit and implicit factors (family, society, training and education process or teacher-student interaction, issues of pattern) which are dominant in the formation of positive and negative attitudes of students of university of technology to the creation and protection of the environment. Conative dimension corresponds to measure of subjective activities of students in this area and refers to the relationship between power factor, evaluation factor and the activity factor in the semantic differential.